2009
DOI: 10.5194/angeo-27-2555-2009
|View full text |Cite
|
Sign up to set email alerts
|

Semidiurnal tidal signature in sporadic E occurrence rates derived from GPS radio occultation measurements at higher midlatitudes

Abstract: Abstract. GPS (Global Positioning System) Radio occultation (RO) measurements from CHAMP, GRACE and FORMOSAT-3/COSMIC satellites at Northern Hemisphere midlatitides (50 • -55 • N) are analysed to obtain the diurnal variation of sporadic E layer occurrence frequency in 2006 and 2007. Interconnections with zonal wind shears measured by meteor radar at Collm (51.3 • N, 13 • E), Germany, are investigated. According to theory, maximum E s occurrence is expected when the zonal wind shear, which is mainly produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 23 publications
13
108
0
Order By: Relevance
“…They suggested that tidal activity may have an influence on the generation of these structures because descending Es layers reflect wind shear, produced when winds at heights above the Es layer have changed directions, due to migrating tides. This seems to be supported by Haldoupis et al (2004), Arras et al (2009) andFytterer et al (2014), who have shown that diurnal, semi-diurnal and terdiurnal tides are the main drivers of Es layers by providing large vertical wind gradients, i.e. wind shear.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…They suggested that tidal activity may have an influence on the generation of these structures because descending Es layers reflect wind shear, produced when winds at heights above the Es layer have changed directions, due to migrating tides. This seems to be supported by Haldoupis et al (2004), Arras et al (2009) andFytterer et al (2014), who have shown that diurnal, semi-diurnal and terdiurnal tides are the main drivers of Es layers by providing large vertical wind gradients, i.e. wind shear.…”
Section: Discussionmentioning
confidence: 52%
“…In the presence of the magnetic field the dynamo electric field results in vertical plasma drift, where ions converge into thin and dense plasma layers known as Es layers. Tide-like structures, especially diurnal and semidiurnal tidal components, have been observed in downward-propagating Es layers, confirming that thermal tides are the primary source of wind shear (Haldoupis et al, 2006;Arras et al, 2009;Fytterer et al, 2014). It is also important to note that the E-region dynamo electric field reaches into the F region via the magnetic field lines, where they drive vertical and horizontal plasma drifts.…”
Section: Introductionmentioning
confidence: 84%
“…The RO method delivers a great amount of data on the electron density distribution in the upper and lower ionosphere that are important sources for modernizing the current information over the morphology of the ionosphere and ionospheric processes [44,45]. The RO method has been actively used to study the global distribution of sporadic E-layers in dependence of latitude, longitude, altitude and local time [5,[27][28][29][30][31][32][39][40][41][45][46][47]. These investigations have produced useful data on climatology and the formation process of sporadic E-layers which depend mainly on the Earth's magnetic field and meteor impact according to the theory of the wind shear mechanism of plasma concentration [48][49][50][51].…”
Section: Application Of Gps Ro Methods To Study the Atmosphere And Ionmentioning
confidence: 99%
“…The altitudes of sporadic E-layers have been evaluated as the height of the RO radio ray perigee in recent times [28,[39][40][41]. A relationship between the eikonal (phase path) and amplitude variations in the GPS/MET RO data has been analyzed in [53] and conclusions have been made that (i) the amplitude variations in distinction to the phase of RO signal have a strong dependency on the distance from observation point to the location of an ionospheric irregularity and (ii) the location of the irregularities in the low ionosphere may be determined by measuring the distance between the observation point up to a phase screen which should be located perpendicularly to the RO ray trajectory at its perigee.…”
Section: Application Of Gps Ro Methods To Study the Atmosphere And Ionmentioning
confidence: 99%
See 1 more Smart Citation